Dietary vitamin A restriction affects adipocyte differentiation and fatty acid composition of intramuscular fat in Iberian pigs. (October 2015) - Ayuso, M.; Óvilo, C.; Rodríguez-Bertos, A.; Rey, A.I.; Daza, A.; Fenández, A.; González-Bulnes, A.; López-Bote, C.J.; Isabel, B.
Abstract: The aim of this study was to investigate whether dietary vitamin A level is associated with differences in adipocyte differentiation or lipid accumulation in Iberian pigs at early growing (35.8 kg live weight) and at finishing (158 kg live weight). Iberian pigs of 16.3 kg live weight were allocated to two feeding groups, one group received 10, 000 IU of vitamin A/kg diet (control); the other group received a diet with 0 IU of vitamin A (var) for the whole experimental period. The dietary vitamin A level had no effect on growth performance and carcass traits. The early suppression of vitamin A increased the preadipocyte number in Longissimus thoracis (LT) muscle in the early growth period (P < 0.001) and the neutral lipid content and composition (higher MUFA and lower SFA content) at the end of the finishing period (P < 0.05). Vitamin A restriction in young pigs increases their lipogenic potential without affecting carcass traits. Highlights: Vitamin A restriction did not affect growth or carcass parameters in Iberian pigs. Preadipocyte number increased in growing vitamin A restricted Iberian pigs. Vitamin A restriction led to higher neutral lipid (NL) content in adult pigs. Restricted pigs showed higher MUFA and lower SFA content in NL of LT.